The Effect of of e-Marketing Design and Customer Involvement Capability on Business Performance and Competitive Advantage of MSMEs - Fahmi, Khaerul; Limakrisna, Nandan; Muharam, Hari (Journal of Industrial Engineering & Management Research, 2024)
The aim of this research is to determine and analyze the influence of e-marketing design and customer involvement capability partially or jointly on competitive advantage. To determine and analyze the influence of e-marketing design, customer involvement capability and competitive advantage both partially and jointly on business performance. The method used was a quantitative method and the analysis used was confirmatory factor analysis (CFA) with a total of 200 respondents. Data analysis using Lisrel 8.70 Based on the research results, the following research findings showed that e-marketing design and customer involvement capability have a positive and significant effect on competitive advantage. E-marketing design, customer involvement capability and competitive advantage have a positive and significant effect on business performance